Determinación del comportamiento de la población linfocítica en perros que han sido tratados con autohemoterapia. - Contreras Chávez., Sofía Lilibeth (2023)
A study was carried out whose purpose was to determine the behavior of the lymphocytic population in dogs that have been treated with alternative or neoadjuvant therapy such as autohemotherapy, which is a technique that consists in the extraction of venous blood, which is immediately reinjected by intramuscularly to the same patient from whom it was extracted, the completely randomized experimental design (DCA) was applied to this study as a statistical analysis, in which 10 dogs participated, where 5 of them underwent a treatment with autohemotherapy of 3 ml and to the other 5 the quantity of 5 ml. To evaluate these samples, automated equipment such as the Dymind hematic analyzer was used. The results show that there are differences according to the amounts used, giving the 3 ml treatment as the best option with a total of 3.22 µl/dl lymphocytes in the blood, therefore it shows that there is a stimulation of the immune system to said treatments, but more studies should be carried out in this regard, meanwhile it is determined that the lymphocytes do not increase considerably in their number after carrying out both treatments, that is, they remain within the range.